The Use of Practice Rehearsal Pairs Strategy in Improving Al-Qur'an Reading Ability at SMK Negeri 10 Bandung - Ahmad Subarna; Mumu Munawar; Abdul Holik (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
. Students who stammer in reading the Qur'an or even cannot read at all, are not solely the fault of the students or the teacher, but often this problem is from the model or method used that is less effective and appropriate. Thus, researchers tried to apply the Practice Rehearsal Pairs strategy implemented at SMK 10 Bandung class X. The purpose of this study was to deepen the study of the improvement of the ability to read the Qur'an between the control class and the experimental class. With a research design using a quasy experiment. The sample used is simple random sampling technique, class X Karawitan 3 students totaling 23 students as the experimental class, and class X Karawitan 1 totaling 23 students as the control class. The instruments used in this study used oral tests and written description questions as many as 5 questions that contained indicators of the ability to read the Qur'an. The results showed that using the mann whitney test obtained a significance value of 0.000 <0.05, which means that there is a significant difference in the improvement of the ability to read the Qur'an between the experimental class and the control class. So it can be concluded that the Practice Rehearsal Pairs strategy has an effect in improving the ability to read the Qur'an in students.